PENERAPAN PENDEKATAN PEMBELAJARAN KONSTEKTUAL BERBASIS MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR TOLAK PELURU GAYA OBRIEN SMP NEGERI I TUGU KABUPATEN TRENGGALEK - Kasmaji Kasmaji (IKIP PGRI Jember, 2017)
Efforts that need to be done by teachers to improve process quality and student learning outcomes include implementing various learning model ever applied by education experts in learning in school.The study was conducted by applying contextual learning approach to image-based media to improve learning outcomes shot-put Obrienstyle.This research uses 2 cycles research design. In each cycle carried out the planning stage, the implementation of the action, observation and reflection. The research subjects of the students of grade VIII E SMP Negeri 1 Tugu Kabupaten Trenggalek consisting of 32 students. The results showed that the application of contextual learning approach based on image media can improve learning result by 10%.